ASPECTOS REGIMENTAIS DO COMITÊ DA BACIA DO PARANÁ III : bases para se pensar a gestão ambiental integrada - Maril Renate Von Borstel Roesier (Revista de Políticas Públicas, 2005)
In the beginning of the twenty-first century, the environmental management gets more complex because of the reduction of water, reflecting on the different ways of organization of human life and other species, through the agricultural, urban and industrial developing processes and a unique access te petable water. Emphasizing that water is the essential component te life’s continu’ty, that is, without water there is no USe. The drarnatic future of the civilization is the government, society and academy’s responsibilitv, this way they should produce effective modeis of adequated using ol water The article searches te detach the chailenges that committees have when talking about the actians done for hydroaph’cs basin. as the proposais to Parana Ilis basin, located in the State of Parana to the coilective appointments in defense of the multiple and sustainable usage of water as countersigns the 2 lst Global Agenda.